Optimization of flammability and thermo-physiological comfort properties in fire-fighter's protective clothing using VIKOR technique - Hafsa Jamshaid; Rajesh Kumar Mishra; Miroslav Muller; Naseer Ahmad; Muhammad Ijaz; Muhammad Shoaib; Vijay Chandan; Petr Jirku (Results in Engineering)
This work dealt with the study of the effect of different blends of inherently fire-resistant fibers and their woven structures on the functional properties of fire retardant (FR) fabrics for various applications. Several properties of the fabrics including weight, thickness and comfort properties i.e., air permeability, moisture management were investigated beside flame-resistant performance. Heat transfer by convection, conduction and radiations were investigated. In this study VIKOR method was used to solve multi response problems. In this method, the signal to noise (S/N) ratio was computed and then converted into process performance index by applying VIKOR method so the (fabric structure/blend proportion) combination which could be ranked and the best of them was selected. Contribution of each factor was also investigated by analysis of variance (ANOVA) and it was concluded that both the factors are important but fiber blend proportion is more important as its contribution was found to be approximately 54 % while the fabric structure had a contribution of 25 %. The sample with 70 % Nomex and 30 % carbon fiber blend and Matt weave was found to be the best in terms of the multi-response analysis. The second-best sample was with 100 % Nomex fiber and Matt weave structure followed by the sample with 70 % Nomex and 30 % Protex fiber having Matt weave structure. Two-way ANOVA was also performed to analyze the combined effect of fiber blend and weave structure on various flammability and comfort aspects. The interaction effect was found to be significant with a P-value of 0.00. This study will be helpful to improve the properties of firefighter's protective fabrics and provide guidelines in terms of comfort and performance while designing their protective clothing for different climatic conditions.